2014
DOI: 10.1002/mabi.201400246
|View full text |Cite
|
Sign up to set email alerts
|

Cell Motility on Polyethylene Glycol Block Copolymers Correlates to Fibronectin Surface Adsorption

Abstract: Adhesion and motility of cells on polyethylene glycol (PEG) engineered surfaces are of fundamental interest for the development of biotechnological devices. Here, the structure of PEG block copolymers physisorbed to surfaces by polyLlysine (PLL) or polypropylene oxide (PPO) is studied. Cell behavior on such surfaces incubated with fibronectin (FN) is analyzed via time-lapse microscopy, the amount and the location of FN is determined via neutron reflectivity. While FN does not adsorb onto PPOPEG, 0.4-0.7 mg m(-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…As expected, fibronectin adsorption was decreased by the presence of the PEG coating, as measured by the reduction in the XPS N 1s signal (Table 3); however, protein adsorption was not totally blocked, and all conditions showed nitrogen values ranging from~2% to 5%. These results are in agreement with the studies of Altankov et al and Röttgermann et al [58,59], which showed the capability of PEG coatings to adsorb, to some extent, fibronectin, and facilitate a certain degree of cell adhesion, making the coatings viable for tissue integration applications, such as dental implants. As such, cell adhesion studies with HFFs showed that PEGylated surfaces were still able to support moderate to good levels of both cell attachment and spreading (Figure 4).…”
Section: Discussionsupporting
confidence: 92%
“…As expected, fibronectin adsorption was decreased by the presence of the PEG coating, as measured by the reduction in the XPS N 1s signal (Table 3); however, protein adsorption was not totally blocked, and all conditions showed nitrogen values ranging from~2% to 5%. These results are in agreement with the studies of Altankov et al and Röttgermann et al [58,59], which showed the capability of PEG coatings to adsorb, to some extent, fibronectin, and facilitate a certain degree of cell adhesion, making the coatings viable for tissue integration applications, such as dental implants. As such, cell adhesion studies with HFFs showed that PEGylated surfaces were still able to support moderate to good levels of both cell attachment and spreading (Figure 4).…”
Section: Discussionsupporting
confidence: 92%
“…Focal adhesions stimulate actin polymerization in lamellipodia and are therefore needed to form protrusions and maintain cell polarization4. Thus, the small number of adhesion points provided on PEG areas54 can explain the switch from run to rest state at the fibronectin/PEG interface.…”
Section: Resultsmentioning
confidence: 99%
“…This single cell platform allows events in hundreds of cells to be followed in parallel. Single cell arrays are obtained via micro-patterned structured surfaces, upon which cells self-organise into an ordered array (Röttgermann et al 2014a(Röttgermann et al , 2014b. In short, polydimethylsiloxane (PDMS) stamps were placed in 8well slides (ibidi GmbH, Martinsried, Germany) as a mask and selectively treated with oxygen plasma, 40 W for 3 min (Femto Diener, Ebhausen, Germany).…”
Section: Ht/c Assays At Lmumentioning
confidence: 99%